PENYUSUNAN LAPORAN KEUANGAN PADA TOKO BERKAH JAYA PLASTIK PERIODE JANUARI 2024 - Octaviany, Featy; Bakri; Elfa Eviolina; Retno Widowati (ASIAN PUBLISHER, 2024)
The purpose of this final assignment is to find out the transaction recording and financial report preparation of the berkah jaya plastik shop. The research method used by the author is a qualitative descriptive method. The data collection technique was carried out through observation of the berkah jaya plastik shop for one month and conducting direct interviews with the shop owner. The results of the observation showed that the berkah jaya plastik shop still recorded transactions manually using a notebook and had not prepared financial reports. Thus, it is not possible to know for sure the financial condition and performance of the business. Based on the results of the author's observations, it can be concluded that the owner of the berkah jaya plastik shop needs training to record transactions and prepare financial reports because the berkah jaya plastik shop has not been able to apply the accounting cycle to its business.